Perceived Effects of Texting and the Spelling Skills of High School Students in Misamis University - Aclao, Joel; Aclao, Ashley Faye A.; Estrada, Ken Willem S.; Pahayahay, Adrian Michael Y.; Regalado, Shantee Nicole G.; Tomo, Gina A. (JPAIR Multidisciplinary Research, 2013)
Text messaging or texting is economical and fastest means of exchanging written messages, hence, become popular and affordable to students. Its limited characters make texters follow a system of texting called “textese” as to its effects to users. This study examined the relationship between the perceived effects of texting and the spelling skills of the high school students in Misamis University. The results show that the students are highly aware of the positive and negative effects of texting. The students have a good level of spelling skills despite being avid texters. The study failed to gather evidences to associate the perceived effects of texting and the spelling skills of the students. However, students revealed that texting disturbs their study time, and they use texting in classroom cheating. The study calls for a regulation on the use of mobile phones during classes as this could be used by the students in academic dishonesty.
Keywords: Texting; Cellular Phone; Texters and Textese; Perceived Effects; Spelling Skills; Descriptive-Correlational Study